Case Study of Digital-Based Service Innovation for Old Age Insurance (JHT) Claims by BPJS Employment (BPJAMSOSTEK) Pekalongan Branch Office Central Java - Maya Sofiana; Juandy Seiver Langelo; Endang Supriyadi; Anita Maulina; Rita Wahyuni (Yayasan Ilomata, 2022)
Various government efforts to break the Covid-19 chain have also affected the economy, as many companies have laid off employees on a large scale. This has resulted in an increase in the number of claims for the Social Security Administering Body (BPJS) for Employment or BPJAMSOSTEK. The purpose of the study was to find out a Case Study of Digital-Based Service Innovation for Old Age Security Claims (JHT) by BPJS Ketenagakerjaan (BPJAMSOSTEK) Pekalongan Branch Office, Central Java. Research methods. The research method used to describe the problems that exist in this study is a qualitative method with a study approach. Primary data sources in this study came from interviews with informants. The informants in this case are employees who are directly involved in the implementation of public services, leaders and participants as users of services provided by BPJAMSOSTEK Pekalongan City Branch, Central Java. The technique used in this study was carried out in several steps, namely, data reduction (sorting, focusing and attention), data presentation (display) and drawing conclusions. Research result. The innovation attributes at BPJAMSOSTEK Pekalongan City Branch are in accordance with the relative advantage, suitability, complexity, possibility to try and ease of observation. In terms of acceptance of the information system, it is seen from 2 elements, namely the ease of use and the usefulness of the LAPAKASIK information system in accordance with the Theory Technology Acceptance Model (TAM): In the Internal User/BPJAMSOSTEK Aspect In the External Aspect User/BPJAMSOSTEK Participant.